Chemical constituents from Kandelia candel with their inhibitory effects on pro-inflammatory cytokines production in LPS-stimulated bone marrow-derived dendritic cells (BMDCs). Issue 7 (1st April 2015) - Dat, Le Duc; Thao, Nguyen Phuong; Tai, Bui Huu; Luyen, Bui Thi Thuy; Kim, Sohyun; Koo, Jung Eun; Koh, Young Sang; Cuong, Nguyen The; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Kiem, Phan Van; et al.
Graphical abstract: Abstract: Chemical investigation of Kandelia candel resulted in the isolation of 19 compounds (1 –19 ), including one new sesquiterpene glycoside, kandelside (1 ), three megastigman glycoside compounds (7 –9 ), 16 known phenolic compounds (2 –6 and10 –19 ). Structures of the isolated compounds were elucidated based on spectral data comparison with reported values. Isolated compounds were also evaluated for their inhibitory effects on the production of pro-inflammatory cytokines interleukin (IL)-12 p40, IL-6, and tumor necrosis factor α (TNF-α) in lipopolysaccharide (LPS)-stimulated bone marrow-derived dendritic cells. Among these compounds, compound9 exhibited strong inhibitory activity against IL-6 production (IC50  = 0.07 ± 0.05 μM) and moderate inhibitory activity against TNF-α production (IC50  = 49.86 ± 1.02 μM), but exhibited no activity on IL-12 p40 production. Compounds5 and6 significantly inhibited IL-12 p40, IL-6, and TNF-α production with IC50 values of 11.68 ± 0.38, 44.52 ± 1.08, and 28.73 ± 0.96 μM, respectively.